If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(3x + -1) = 30 Reorder the terms: 3x(-1 + 3x) = 30 (-1 * 3x + 3x * 3x) = 30 (-3x + 9x2) = 30 Solving -3x + 9x2 = 30 Solving for variable 'x'. Reorder the terms: -30 + -3x + 9x2 = 30 + -30 Combine like terms: 30 + -30 = 0 -30 + -3x + 9x2 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-10 + -1x + 3x2) = 0 Factor a trinomial. 3((-5 + -3x)(2 + -1x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-5 + -3x)' equal to zero and attempt to solve: Simplifying -5 + -3x = 0 Solving -5 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -3x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -3x = 0 + 5 -3x = 0 + 5 Combine like terms: 0 + 5 = 5 -3x = 5 Divide each side by '-3'. x = -1.666666667 Simplifying x = -1.666666667Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Solution
x = {-1.666666667, 2}
| -5(2x-2)=2(1-4x) | | 3u+2w=11 | | 7-3a=-2(-7+2a) | | 3n-5+6n-17=167 | | 2(1+7r)+5r=2+7r | | x^2=-24x | | -2-4a=6-a-3a | | -2-4a=6-a | | 6-7x=-7+6 | | (x-y)(x^2-7xy+y^2)=0 | | 30x+2=902 | | 31=-8(3n-2)-3(4+n) | | (3v^4+6v)-5v^4-4v+8= | | -6=-4x+7x | | (6x+11)*log(4)=(x-1)*log(16) | | 103=8(7-m)+7 | | 4n+42+n-100=2942 | | 103=8(3n-2)-3(4+n) | | 4z=1.7+4.3 | | x^2-3*x=22 | | x^2-3*tan(4*3x)=12 | | 5+3a+3=23 | | 0.8p=-112 | | x+9-2sqrtx+24=0 | | log(5x+7)=1+log(x-6) | | 7y=6(y+6) | | 3x-4x=65 | | 5(2+3x)-1=-6 | | (x+3y)(5x+3y)= | | (4y+2)(4-y)=0 | | 2z=1.8+0.8 | | 56=14y-7y |